Climate change and ecosystems : challenges to sustainable development - Fahad, Shah ; Adnan, Muhammad ; Saud, Shah ; Nie , Lixiao (CRC Press, Boca Raton, FL, 2003)
"The global population is projected to increase by 3.3 billion, from 6.7 to 10 billion during 2008 to 2100. As a result, soil degradation and desertification are growing due to the increasing demand of the food, feed, fiber and fuel on finite soil resources. The problem of global food insecurity may be further worsened by the threat of global warming. Climate change is showing its impacts in term of increasing temperatures, variable rainfall and an increase in climate-related extreme like floods, droughts, cyclone, sea level rise, salinity and soil erosion. Agriculture sector is the most sensitive to the climate changes because the climate of a region/country determines the nature and characteristics of vegetation and crops. Increase in the mean seasonal temperature and decrease in effective precipitation can reduce the duration of many crops, may lead to outbreaks of pests and diseases, and hence reduce final yield ultimately affecting the food security of the country. Despite the positive impact of CO2 fertilization, the net productivity may decrease because of an increase in respiration rate, drought stress and nutrient deficiency. Such as, for every 75 ppm increase in CO2 concentration rice yields will increase by 0.5 t ha-1, but yield will decrease by 0.6 t ha-1 for every 1 °C increase in temperature. The global agricultural productivity is expected to decrease from 3-16 % by 2080. The estimated decrease in agricultural productivity in the developing countries is 10-25% in 2080s, where average air temperature has already near or above crop tolerance levels. This book is intended to serve as a stimulating collection that will contribute to debate and reflection on the sustainable future of agriculture and food production in the face of global change. Features: Brings together a multidimensional group of international scholars exploring the ethical dimensions of climate change and ecosystem. New strategies have pointed in this book for the better sustainable development. Design to cater a good overview of major challenges facing policy makers, researchers and ultimately humankind in dealing with climate change. This book summarizes the diverse features of vulnerability, adaptation, and amelioration of climate change in respect to plants, crops, soil, and microbes for the sustainability of the agricultural sector and, ultimately, food security for the future. Provide a state-of-the-art description of the physiological, biochemical, and molecular status of the understanding of abiotic stress in plants"-- Provided by publisher